Doses of silicon in the induction of water stress tolerance in Moringa oleifera Lam. (Research, Society and Development, 2022)
Moringa oleifera Lam. It is a multiple uses plant, whether used as human food (flowers, leaves, fruits and seeds) and animal (forage production), water treatment for human consumption, cosmetics and medicine industry, fuel, paper production. It is considered an exotic tree species that has adapted to the edaphoclimatic conditions of the semiarid region of the Brazilian Northeast, although the occurrence of water deficit reduces growth, limits development and compromises the physiology of the plant. Silicon is a water deficit mitigating agent. The objective of the present study was to evaluate the effect of silicon doses in inducing the tolerance of Moringa oleifera to water stress, on vegetative growth. The study was developed in partnership with the Center for Agricultural and Environmental Sciences of the State University of Paraíba, located in the municipality of Lagoa Seca - PB. The experiment was set up in a randomized block design, in split plots in a 5x5 double factorial scheme, with five irrigation depths (25, 50, 75, 100 and 125% of ETc) and five silicon doses (0, 3, 6 , 9 and 12 g of silicon dioxide per plant), totaling 25 treatments with four replications, with 100 experimental units which consisted of three useful plants. In the plots were the irrigation depths and in the sub-plots were the silicon doses. Irrigation depths exerted a significant influence on all growth variables studied.